2009
DOI: 10.1007/s00441-009-0801-2
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine reduces testicular damage in rats treated with etoposide in the prepubertal phase

Abstract: Etoposide is a chemotherapeutic agent that induces cell death by blocking topoisomerase II catalytic function. Although etoposide is effective in the treatment of cancer, it also causes the death of normal proliferating cells, including male germ cells. Administration of etoposide during the prepubertal phase causes diturbances in several testicular morphometric parameters and in Sertoli cells. Cytoprotection of the seminiferous epithelium is the only means of preserving potential male reproduction in prepuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…Thus, the present results corroborate the antiapoptotic role of carnitine and reinforce the improved outcomes of quantitative and qualitative sperm parameters noticed in the carnitine+doxorubicin-treated rats. Similar results were obtained by our group when carnitine was previously administered to etoposide, providing significantly lowered the number of apoptotic germ cells and improved morphometric and stereological testicular parameters (Okada et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Thus, the present results corroborate the antiapoptotic role of carnitine and reinforce the improved outcomes of quantitative and qualitative sperm parameters noticed in the carnitine+doxorubicin-treated rats. Similar results were obtained by our group when carnitine was previously administered to etoposide, providing significantly lowered the number of apoptotic germ cells and improved morphometric and stereological testicular parameters (Okada et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies using L-carnitine pre-treatment, our group showed a significantly lower incidence of apoptosis in germ cell caused by etoposide (Okada et al, 2009), pointing out for a broader usage of this compound. Considering those results, this study aimed to investigate whether carnitine pre-treatment protects the pre-pubertal seminiferous epithelium from the damages induced by doxorubicin and whether such protection can lead to an improvement in spermatic parameters and testicular integrity in the adult phase.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In comparison to etoposide group, co-administration with LC ameliorated histological and histomorphometrical alterations, concentration of spermatozoa, and sperm abnormal morphology. However, the authors thought that proving the injurious effects of etoposide in pre-pubertal condition is the most achieved findings, and the protective effects of LC must be confirmed in further investigation (34).…”
Section: L-carnitine and Chemotherapy Induced Infertilitymentioning
confidence: 99%